2019
DOI: 10.1111/vsu.13320
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave therapy improves short‐term limb use after canine tibial plateau leveling osteotomy

Abstract: Objective To determine the influence of postoperative extracorporeal shock wave therapy (ESWT) on hind limb use after tibial plateau leveling osteotomy (TPLO). Study design Randomized, prospective clinical trial. Animals Sixteen client‐owned dogs, 2 to 10 years old weighing 18 to 75 kg. Methods Dogs were randomly assigned to treatment cohorts, TPLO with ESWT (ESWT, n = 9) or TPLO without ESWT (control, n = 7). Treatment consisted of 1000 pulses at 0.15 mJ/mm2 immediately and 2 weeks after surgery. Subjective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…The loss of joint motion and muscle atrophy are two common consequences of joint disease 1‐5 . In osteoarthritic joints, all tissues of the joint are subject to substantial alterations.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of joint motion and muscle atrophy are two common consequences of joint disease 1‐5 . In osteoarthritic joints, all tissues of the joint are subject to substantial alterations.…”
Section: Introductionmentioning
confidence: 99%
“…9 Researchers in a subsequent study reported that dogs treated with liposomal bupivacaine after tibial plateau leveling osteotomy (TPLO) required significantly lower rescue doses of opioids compared with dogs treated with 0.5% bupivacaine HCl. 10 Extracorporeal shock wave therapy (ESWT) has been described as an effective nonpharmaceutical alternative to regional analgesia in man 14 and dogs 15,16 with orthopedic disease. Extracorporeal shock wave therapy is a focused, high-energy sound wave treatment initially used for lithotripsy, 17 although the device used for lithotripsy varies from orthopedic shock wave devices.…”
Section: Introductionmentioning
confidence: 99%
“…Extracorporeal shock wave therapy is a focused, high-energy sound wave treatment initially used for lithotripsy, 17 although the device used for lithotripsy varies from orthopedic shock wave devices. Extracorporeal shock wave therapy has been reported in veterinary medicine as effective for various conditions including an increase in short-term limb use after TPLO 15 and in treatment of tendinopathies 18,19 and osteoarthritis. [16][17][18][19][20] Extracorporeal shock wave therapy was also shown to accelerate bone healing after TPLO when treatment was performed at the surgical site immediately after incision closure and again at the time of suture removal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A tibial plateau levelling osteotomy (TPLO) represents the best way to treat CCLD, despite more than 5 decades since the first surgical treatment described for this condition (Barnes et al 2019;Nanda and Hans 2019;Clark et al 2020;Vezzoni et al 2020). The magnitude of the cranial tibial impulse Veterinarni Medicina, 66, 2021 (02): 58-65 https://doi.org/10.17221/128/2020-VETMED (0° to 14°) (Warzee et al 2001;Reif et al 2002;Nanda and Hans 2019).…”
mentioning
confidence: 99%